Vitamin B12 may prevent Aβ oligomer‐induced neurotoxicity in Alzheimer's disease: Nonhuman/Lead optimization studies. (7th December 2020) - Kimura, Atsushi Michael; Tsuji, Mayumi; Yasumoto, Taro; Oguchi, Tatsunori; Mori, Yukiko; Yano, Satoshi; Kinnno, Ryuta; Nakamura, Shiro; Inoue, Tomio; Teplow, David B.; Kiuchi, Yuji; Ono, Kenjiro
Abstract: Background: Excessive accumulation of β‐amyloid peptide (Aβ) is one of the major mechanisms that cause neuronal death in Alzheimer's disease (AD). We've previously shown protofibrils, one of the accumulated Aβ oligomers, are implicated to play a major role. Vitamin B12 (VB12) is an important micronutrient required for brain development and has received attention because of its ability to improve cognitive status in Mild Cognitive Impairment(MCI).However, the protective effects of VB12 against Aβ oligomer‐induced neurotoxicity remain unclear. Recently, we found blood VB12 levels in AD patients are significantly associated with some of the major cognitive functions. Besides, it was associated with left hippocampal blood flow.The purpose of this study was to clarify the mechanism of the protective effect of VB12 against the Aβ oligomer‐induced neurotoxicity. Method: Aβ(1‐42) oligomer was eluted using size exclusion chromatography. Neuronal damage was induced in human neuroblastoma cells (SH‐SY5Y) using 5 μM Aβ oligomer. SH‐SY5Y cells were treated with VB12 (50 μM) for 30 min ‐3 hours in combination with Aβ oligomer. Cytotoxicity of Aβ oligomer‐exposed cells was assessed by the 3‐[4, 5‐dimethylthiazole‐2‐yl]‐2, 5‐diphenyltetrazolium bromide (MTT) and mitochondrial membrane potential (MMP) analyses. Oxidative stress was evaluated by measuring products of reactive oxygen species (ROS), mitochondrial ROS and phospholipid peroxides of plasma cell membranes. Result: Aβ oligomers (1, 2.5, 5 and 10 μM) exposure decreased cell viability in a dose‐dependent manner. However, treatment with VB12 significantly recovered the cell viability that was reduced by treatment with Aβ oligomer. MMP significantly decreased with Aβ oligomer and the decrease was significantly suppressed with treatment with VB12, indicating that mitochondria were involved in the neuronal damage induced by Aβ oligomer exposure. Aβ oligomer increased intracellular ROS, mitochondrial ROS and phospholipid peroxides of the plasma membrane, and the increase in Aβ oligomer‐induced oxidative stress was reduced by VB12 treatment. Conclusion: These results suggested that the collapse of mitochondria induced by oxidative stress associated with Aβ oligomer exposure was suppressed by treatment with VB12. VB12 may be provided as a therapeutic agent for the prevention of neuronal damage and as a candidate for the treatment of cognitive impairments in AD patients.